2019
DOI: 10.34194/geusb-201943-02-07
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary landslide mapping in Greenland

Abstract: The landslide of 17 June 2017 in Karrat Fjord, central West Greenland, highlighted the need for a better understanding of landslides and landslide-generated tsunamis in Greenland and motivated a landslide screening project in 2018, led by the Geological Survey of Denmark and Greenland (GEUS; see also Svennevig et al. this volume). A central part of this project was to conduct a preliminary mapping of Quaternary and historical landslides in Greenland-the first effort of its kind. The main objective was to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…A similar approach could also be implimented to quantify activity in other remote areas that are prone to landslides. An obvious candidate is the south coast of the Nuussuaq peninsular where several catastrophical historical and prehistorical landsides are known to have occurred (Pedersen et al 2002;Dahl-Jensen et al 2004;Svennevig 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach could also be implimented to quantify activity in other remote areas that are prone to landslides. An obvious candidate is the south coast of the Nuussuaq peninsular where several catastrophical historical and prehistorical landsides are known to have occurred (Pedersen et al 2002;Dahl-Jensen et al 2004;Svennevig 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Two tsunami-generating rock avalanches in 1952 and 2000 are described from Vaigat, 150 km to the south of Karrat (Pedersen et al, 2002;Dahl-Jensen et al, 2004). Svennevig (2019) described morphological evidence of several Holocene rock slope failures in the region but noted that the majority of these were located in the area of the Cretaceous-Paleogene Nuussuaq Basin, where the 1952 and 2000 rock avalanches also occurred. The geological province where the 2017 rock avalanche occurred was found to have had relatively few rock slope failures (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Following the launch of Landsat 8 and Sentinel-1 and Sentinel-2 satellites, optical and ground motion data over Greenland are both free and frequent and at sufficient resolution, providing a means of observing unstable slopes at relatively low cost. Svennevig et al (2019) preliminarily described a multidisciplinary approach combining satellite data and seismic observations to remotely study activity on an unstable slope. They found that by combining these methods it was possible to reliably detect timing (seismic observations), location, extent, and deformational rates (optical images and ground motion observations from DInSAR (differential interferometric synthetic-aperture radar)) of rock slope failures.…”
Section: Introductionmentioning
confidence: 99%
“…But most of the time they are only available for limited areas (Guzzetti et al 2012). Moreover, inventories should be regularly updated, complemented by historical databases to consider the geographical distribution of past (Svennevig 2019) and recent landslides in different time periods (location of the hazard initiation and extension, age…). The regular updating of inventories is also complicated and requires large effort (Bell et al 2012;Burns and Madin 2009;Burns et al 2012;Galli et al 2008;Guzzetti et al 2012) especially for inaccessible high altitude areas (Du et al 2020).…”
Section: Earth Observation Data and Methods For Landslide Detection Amentioning
confidence: 99%